Freshwater crabs from eastern Panamá: a new species of Potamocarcinus H. Milne Edwards, 1853, and new records of two little-known species (Crustacea: Decapoda: Pseudothelphusidae, Trichodactylidae) - Magalhães, Célio; Campos, Martha R.; Türkay, Michael (Zootaxa, 2013)
A small collection of freshwater crabs from eastern Panamá revealed a new species of pseudothelphusid crab, Potamocarcinus darienensis n. sp., which is described and illustrated. The new species is characterized by an unusual arrangement of distal processes in the male first gonopod, in which the mesial lobe is folded in a latero-cephalic direction over the apex and the apex is broadened by a rounded protuberance in its caudo-lateral surface, the cephalic surface having a small, conical median cephalic process, and a large, prominent, subtriangular proximal cephalic process. New records of two little-known species described from eastern Panamá, Spirocarcinus garthi (Pretzmann, 1971) (Pseudothelphusidae) and Melocarcinus meekei (Pretzmann, 1968) (Trichodactylidae), are listed and the first gonopod of S. garthi is redescribed.